Skeletal muscle-specific overexpression of miR-486 limits mammary tumor-induced skeletal muscle functional limitations - Ruizhong Wang; Brijesh Kumar; Emma H. Doud; Amber L. Mosley; Matthew S. Alexander; Louis M. Kunkel; Harikrishna Nakshatri (Molecular Therapy: Nucleic Acids, 2022)
miR-486 is a myogenic microRNA, and its reduced skeletal muscle expression is observed in muscular dystrophy. Transgenic overexpression of miR-486 using muscle creatine kinase promoter (MCK-miR-486) partially rescues muscular dystrophy phenotype. We had previously demonstrated reduced circulating and skeletal muscle miR-486 levels with accompanying skeletal muscle defects in mammary tumor models. To determine whether skeletal muscle miR-486 is functionally similar in dystrophies and cancer, we performed functional limitations and biochemical studies of skeletal muscles of MMTV-Neu mice that mimic HER2+ breast cancer and MMTV-PyMT mice that mimic luminal subtype B breast cancer and these mice crossed to MCK-miR-486 mice. miR-486 significantly prevented tumor-induced reduction in muscle contraction force, grip strength, and rotarod performance in MMTV-Neu mice. In this model, miR-486 reversed cancer-induced skeletal muscle changes, including loss of p53, phospho-AKT, and phospho-laminin alpha 2 (LAMA2) and gain of hnRNPA0 and SRSF10 phosphorylation. LAMA2 is a part of the dystrophin-associated glycoprotein complex, and its loss of function causes congenital muscular dystrophy. Complementing these beneficial effects on muscle, miR-486 indirectly reduced tumor growth and improved survival, which is likely due to systemic effects of miR-486 on production of pro-inflammatory cytokines such as IL-6. Thus, similar to dystrophy, miR-486 has the potential to reverse skeletal muscle defects and cancer burden.